From Blogger to Book Author: Examining Self-Publishing, Self-Presentation and Discourse in Travel Blogs - Azariah, Deepti (ANZCA, 2014)
For publishers, blogs that enjoy a wide readership are new sources of talent that may be developed into potentially bestselling books (Nelson, 2006: 6; Pedersen, 2009: 98; Williams, 2010: 6). This blog-to-book or ‘blook’ phenomenon is best exemplified in publications such as The Intimate Adventures of a London Call Girl and Julie and Julia: My Year of Cooking Dangerously, blog-based books that went on to be cinematised (Pedersen, 2009: 95). Given the success of such publications, and the view that publishing a book is one way to monetise a blog, it is not surprising that for a number of individuals blogging is a logical first step to attracting a publisher’s attention and signing a book deal (Pedersen, 2009: 95; Williams, 2010: 7). Against this background, this paper examines how some travel bloggers who aspire to be traditionally published authors develop their blogs into books. The studies and the successful book deals mentioned earlier suggest that for their authors these travel blogs could possibly be a point of entry into the field of book publishing and facilitate access to recognised publishers of print books. Yet, for those unable to land a lucrative contract, self-publishing services such as Lulu offer a viable alternative to getting one’s name in print (Martin and Tian, 2012: 87). Taking a Goffmanian approach, this study considers the role of self-publishing in the evolution of a travel blog into a print book or e-book and its implications for a travel blogger’s presentation of self as a published author. It also examines travel blogs as narratives of self-presentation, which constantly negotiate discourses of travel and tourism, and finds that publishing a travel blog as a book commercialises these narratives and introduces an element of touristic discourse. Turning a blog into a book therefore has several implications for these bloggers’ presentation of the self as travellers and as published authors.